2020
DOI: 10.2131/jts.45.109
|View full text |Cite
|
Sign up to set email alerts
|

Cell density-dependent modulation of perlecan synthesis by dichloro(2,9-dimethyl-1,10-phenanthroline)zinc(II) in vascular endothelial cells

Abstract: Proteoglycans that are synthesized by vascular endothelial cells contribute to the proliferation, migration, and blood coagulation-fibrinolytic system in vascular endothelial cells. Clarification of the molecular mechanisms for proteoglycan synthesis allows understanding of the regulation of endothelial functions. The research strategy of bioorganometallics analyzes biological systems using organic-inorganic hybrid molecules as tools. The present study found dichloro(2,9-dimethyl-1,10-phenanthroline) zinc(II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The structure of Cu10 is shown in Figure 1a. Because the response of vascular endothelial cells to exogenous factors is often cell density-dependent [32][33][34][35][36], both dense and sparse cultures of the cells were used in this experiment. CSE protein expression was not altered by Cu10 in dense (Figure 1b (Figure 1d, lower panels) cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of Cu10 is shown in Figure 1a. Because the response of vascular endothelial cells to exogenous factors is often cell density-dependent [32][33][34][35][36], both dense and sparse cultures of the cells were used in this experiment. CSE protein expression was not altered by Cu10 in dense (Figure 1b (Figure 1d, lower panels) cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, IL-1α induces perlecan synthesis in other cell types, such as rabbit corneal stromal cells [ 30 ] and mouse hippocampal cells [ 31 ], although whether the length and disaccharide composition of heparan sulfate chains are altered by the cytokine is unknown. Recently, we found that 2,9-dimethyl-1,10-phenanthroline and dichloro(2,9-dimethyl-1,10-phenanthroline)zinc(II) modulate endothelial perlecan synthesis [ 25 ]. These two compounds increase perlecan synthesis in cultured bovine aortic endothelial cells when the cell density is high; however, the level of perlecan mRNA is unaffected by the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, we reported a small molecule that can modulate endothelial proteoglycan species such as diethyldithiocarbamate copper(II) and 1,10-phenanthroline, both of which induce endothelial syndecan-4 expression via the p38 MAPK and hypoxia-inducible factor (HIF)-1α pathways, respectively [ 23 , 24 ]. Additionally, we had recently reported a zinc complex dichloro(2,9-dimethyl-1,10-phenanthroline)zinc(II) that upregulates perlecan in a cell density dependent manner; however, this activity was due to its organic structure [ 25 ]. Therefore, we considered that an organoantimony compound PMTAS may affect endothelial perlecan synthesis owing to its nontoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine aortic endothelial cells, which have been widely used in PG research [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ], at 23–30 passages were cultured in a humidified atmosphere of 5% CO 2 at 37 °C in DMEM supplemented with 10% fetal bovine serum (FBS) in 35-mm dishes until 80% confluence. The cells were then incubated for 8 h at 37 °C in fresh DMEM supplemented with 10% FBS in the presence of the siRNA/Lipofectamine RNAiMAX mixture prepared as described previously [ 17 ].…”
Section: Methodsmentioning
confidence: 99%